Ghost Ileostomy in Advanced Ovarian Cancer: A Reliable Option. Issue 7 (1st September 2018) - Lago, Víctor; Flor, Blas; Matute, Luis; Padilla-Iserte, Pablo; García-Granero, Alvaro; Bustamante, Marco; Domingo, Santiago
Abstract : Objective: Diverting ileostomy (DI) has been proposed to reduce the incidence and consequences anastomotic leakage after bowel resection. In colorectal cancer treatment, ghost ileostomy (GI) has been proposed as an alternative to DI. Our objective was to report the results of GI associated with colorectal resection in the treatment of ovarian cancer. Materials and Methods: This is an observational pilot study performed in a single institution. The main objective sought was to report the results of GI associated with colorectal resection in the treatment of ovarian cancer: 26 patients were included. Results: Modified posterior exenteration was performed in 24 cases (92.3%) and rectum resection in the 2 cases of relapse (7.7%). After the main procedure GI was created, to check up the anastomosis status, a sequential postoperative rectoscopy was performed on postoperative day 5 ± 1 (range, 4–7). Serum levels were monitored in first and third postoperative days just with a descriptive intention to establish its relationship with the rectoscopy findings. In 2 cases, rectoscopy demonstrated a leakage. During postoperative course, no other complication related with the GI or DI was observed. No case of clinical anastomotic leakage was found. Conclusions: To the extent of our knowledge, this is the first study in which GI has been performed for the treatment of patients with ovarian cancer. Ghost ileostomy represents a real option that may reduce the number of ileostomies performed in ovarian cancer without increasing the morbimortality. Ghost ileostomy presents the advantages of DI while avoiding its drawbacks. It also seems to be a safe, feasible, and reproducible technique that does not add significant costs to the surgery.